The Relationship of Age and Postoperative Pain in Women Following Surgery for Breast Cancer - Kudach, Christina (Pain Manag Nurs, 2018)
BACKGROUND: In the past, elderly women with breast cancer were not offered surgery because of beliefs that they would experience serious complications from comorbidities and increased chronological age. Today the decision to offer surgery is based on a woman’s fitness rather than her age. OBJECTIVE: The purpose of this study is to compare the experience of postoperative nausea and vomiting (PONV), anxiety and reported pain levels in women who represent four different age groups following breast cancer surgery. METHODS: Postoperative pain was measured in the post-anesthesia care unit (PACU) using an 11-point Verbal Pain Scale, PONV was measured categorically and if present severity of nausea was assessed. Anxiety was measured preoperatively by the short form Profile of Mood States (POMS-SF). FINDINGS: 97 women, aged 37–78 participated in this study. Overall, 35% of all women experienced PONV, however, only two women (18%) in the highest age range (70–79) experienced PONV, yet they reported significantly more pain than women in the other age groups. Understanding the difference in postoperative symptoms experienced by older woman following surgery for breast cancer will support the development of age specific strategies.